Multi-OMICs landscape of SARS-CoV-2-induced host responses in human lung epithelial cells - Pinto, Sneha M.; Subbannayya, Yashwanth; Kim, Hera; Hagen, Lars; Górna, Maria W.; Nieminen, Anni I.; Bjørås, Magnar; Espevik, Terje; Kainov, Denis; Kandasamy, Richard K. (iScience, 2023)
COVID-19 pandemic continues to remain a global health concern owing to the emergence of newer variants. Several multi-Omics studies have produced extensive evidence on host-pathogen interactions and potential therapeutic targets. Nonetheless, an increased understanding of host signaling networks regulated by post-translational modifications and their ensuing effect on the cellular dynamics is critical to expanding the current knowledge on SARS-CoV-2 infections. Through an unbiased transcriptomics, proteomics, acetylomics, phosphoproteomics, and exometabolome analysis of a lung-derived human cell line, we show that SARS-CoV-2 Norway/Trondheim-S15 strain induces time-dependent alterations in the induction of type I IFN response, activation of DNA damage response, dysregulated Hippo signaling, among others. We identified interplay of phosphorylation and acetylation dynamics on host proteins and its effect on the altered release of metabolites, especially organic acids and ketone bodies. Together, our findings serve as a resource of potential targets that can aid in designing novel host-directed therapeutic strategies. [Display omitted] •Performed a multi-OMICs analysis to expand the current knowledge on SARS-CoV-2 infections•Post-translational modifications regulate cell signaling during host antiviral response•SARS-CoV-2 causes activation of DNA damage response and dysregulation of Hippo signaling•Exometabolome analysis showed dysregulated cellular metabolism Virology; Proteomics; Metabolomics; Transcriptomics